Defender [large type] - Palmer, Diana (Palmer, Diana. Long, tall Texans series., 2016)
The man who shattered her trust is back to protect her ... When Paul Fiore disappeared from Isabel Grayling's life, he told himself it was for all the right reasons. She was young and innocent, and he was her millionaire father's lowly employee. Three years on, Paul is the FBI agent assigned to Isabel's case. Too late, he realizes how much damage he did when he left.